The Chinese Herbal Prescription JieZe-1 Inhibits Membrane Fusion and the Toll-like Receptor Signaling Pathway in a Genital Herpes Mouse Model - Duan, Qianni; Liu, Tong; Huang, Cong; Shao, Qingqing; Ma, Yonggui; Wang, Wenjia; Liu, Tianli; Sun, Jun; Fang, Jianguo; Huang, Guangying; Chen, Zhuo (Frontiers in Pharmacology, 2021)
Chinese herbal prescription JieZe-1 is effective for genital herpes with no visible adverse effects clinically. It showed an excellent anti-HSV-2 effect in vitro. However, its mechanism of anti-HSV-2 effect in vivo remains unclear. This study was designed to evaluate the anti-HSV-2 effect of JieZe-1 and berberine in a genital herpes mouse model and explore the underlying mechanism. The fingerprint of JieZe-1 was determined by high-performance liquid chromatography. First, we optimized a mouse model of genital herpes. Next, the weight, symptom score, morphological changes, viral load, membrane fusion proteins, critical proteins of the Toll-like receptor signaling pathway, cytokines, and immune cells of vaginal tissue in mice at different time points were measured. Finally, we treated the genital herpes mouse model with JieZe-1 gel (2.5 g/mL, 1.5 g/mL, and 0.5 g/mL) and tested the above experimental indexes at 12 h and on the 9th day after modeling. JieZe-1 improved the symptoms, weight, and histopathological damage of genital herpes mice, promoted the keratin repair of tissues, and protected organelles to maintain the typical morphology of cells. It downregulated the expression of membrane fusion proteins, critical proteins of the Toll-like receptor signaling pathway, cytokines, and immune cells. The vaginal, vulvar, and spinal cord viral load and vaginal virus shedding were also significantly reduced. In summary, JieZe-1 shows significant anti-HSV-2 efficacy in vivo. The mechanism is related to the inhibition of membrane fusion, the Toll-like receptor signaling pathway, inflammatory cytokines, and cellular immunity. However, berberine, the main component of JieZe-1 monarch medicine, showed no efficacy at a concentration of 891.8 μM (0.3 mg/mL).